INTERPRETATION OF PATRON CHARACTERS IN FOLK EPICS - Feruza Mamatkulova (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the motive of children in the epic "Tahir and Zuhra" and folk tales, as well as patron heroes in the variants and versions of these works in different languages.